The argumentation in Galatians - M. Hietanen (Acta Theologica)
Many exegetes set out to analyse not only rhetorical features in Galatians but also other features relating to Paul’s argumentation. Still, the use of insights from modern argumentation theory has been modest and no full-fledged argumentation analyses of Paul’s argumentation have yet been attempted. However, modern methods for argumentation analysis provide useful tools for such an undertaking. Using the pragmadialectical model of argumentation analysis, this paper illustrates how a modern approach can be used for Galatians. It is argued that by using a sophisticated method we can gain a more accurate understanding of Paul’s argumentation.